Who Pays? Measuring Differences in the Process of Repayment of Legal Financial Obligations - Kathleen Powell (MDPI AG, 2021)
This study identifies the correlates of legal financial obligation (LFO) debt repayment among persons sentenced to probation and transferred to a specialized collections unit. Using bivariate tests and logistic regression, results indicate that starting balance amounts, monthly payment amounts, and enforcement actions (capias warrant) are the strongest influences on the likelihood of full debt repayment. These results indicate that some persons will struggle to repay their LFO balances if amounts assessed are in excess of their means, even in an institutional context adopting an individualized, flexible, and non-punitive approach to collections. Policy implications suggest a need for reform at the point of LFO assessment to avoid imposing obligations that are unreasonable to individuals’ ability to repay.